Bicarbonate Plays a Critical Role in the Generation of Cytotoxicity during SIN-1 Decomposition in Culture Medium. (9th July 2012) - Shirai, Kyo; Okada, Tatsumi; Konishi, Kanako; Murata, Hiroshi; Akashi, Soichiro; Sugawara, Fumio; Watanabe, Nobuo; Arai, Takao
Abstract : 3-Morpholinosydnonimine (SIN-1) is used as a donor of peroxynitrite (ONOO − ) in various studies. We demonstrated, however, that, the cell-culture medium remains cytotoxic to PC12 cells even after almost complete SIN-1 decomposition, suggesting that reaction product(s) in the medium, rather than ONOO −, exert cytotoxic effects. Here, we clarified that significant cytotoxicity persists after SIN-1 decomposes in bicarbonate, a component of the culture medium, but not in NaOH. Cytotoxic SIN-1-decomposed bicarbonate, which lacks both oxidizing and nitrosating activities, degrades to innocuous state over time. The extent of SIN-1 cytotoxicity, irrespective of its fresh or decomposed state, appears to depend on the total number of initial SIN-1 molecules per cell, rather than its concentration, and involves oxidative/nitrosative stress-related cell damage. These results suggest that, despite its low abundance, the bicarbonate-dependent cytotoxic substance that accumulates in the medium during SIN-1 breakdown is the cytotoxic entity of SIN-1.